Sex Comparison of White-Blood-Cell Responses to Acute Vigorous-Intensity Aerobic Exercise - Koivula, Tiia; Neuvonen, Joona; Sucksdorff, Marcus; Kapanen, Jukka; Heinonen, Olli J.; Rissanen, Eero; Heinonen, Ilkka (Human Kinetics, 2026)
Purpose: It is widely accepted that exercise alters the number and function of circulating white blood cells, and many factors are suggested to influence this phenomenon. Previous study populations have primarily been men, so this study aimed to compare mobilization of white blood cells between sexes after an acute exercise bout.
Methods: The study included healthy and physically active participants, 10 men (age 26 [SD 7] y) and 10 women (age 33 [SD 8] y). Participants performed a 30-minute cycling ergometer exercise session at 70% maximal oxygen uptake, and blood samples were drawn at rest and at 3 minutes, 1 hour, and 2 hours postexercise.
Results: Changes in total leukocyte, neutrophil, lymphocyte, monocyte, eosinophil, and basophil counts were analyzed and corrected for plasma volume change. Acute exercise significantly increased the number of total leukocytes and all leukocyte subpopulations excluding eosinophils in both women and men. The mobilization of all leukocyte subpopulations was similar in both sexes, but mobilization of total leukocytes, as a percentage change from baseline, was significantly greater in men (52% [SD 28%] in men, 19% [SD 23%] in women, P = .024, Cohen d = 1.06).
Conclusions: These findings indicate that the sex difference in white-blood-cell mobilization in response to vigorous acute exercise is small and was only evident in total leucocyte response in the present study.
Keywords: gender; immune cells; immunology; leukocyte; mobilization; physical activity.